Generation and utilization of community fund in small-scale community forest management in the Terai region of Nepal - Dhakal, Maheshwar; Masuda, Misa (Banko Janakari, 2009)
It has been widely recognized that constantly increasing community fund is one of the indicators of successful implementation of community forestry program in Nepal. However, a very few people know how the fund is collected under the program and it has been utilized so far. The paper is based on the generation and utilization of community fund of two-community forests in the Terai region. The community forests of the region have collected large amount of community fund annually from the sale of forest products and non-forestry sources as well. The study revealed that along with community fund increasing, office operation cost has been constantly increasing while utilizing the fund, whereas promotion of forest management and community development costs are essential for long-term sustainability of the program. Therefore, the study concluded that only the minimization of office operation cost could increase the forest management and community development costs based on the principle of trade-off, which is crucial to keep the people intact in community forestry program and its long-term sustainability. Keywords: community forestry, community fund, Terai, Nepal   doi: 10.3126/banko.v17i2.2156 Banko Janakari, Vol. 17, No. 2, 55-61